A Least Cumulative Ventilation Cost Method for Urban Ventilation Environment Analysis - Peng Xie; Dianfeng Liu; Yanfang Liu; Yaolin Liu (Complexity)
The correct urban building layout is an important influencing factor in urban ventilation, and the heat island effect has become an important factor affecting the quality of urban life. Optimization of the urban building layout can play a role in mitigating the heat island effect. The traditional ventilation corridor analysis method, based on a least-cost path analysis, can only generate a few main ventilation corridors. It is difficult to obtain global ventilation results covering the whole study area using this method of analysis. On the basis of urban morphology and a least-cost path analysis, this study proposes a “least cumulative ventilation cost” method for analyzing urban ventilation. Taking Wuhan downtown as a research area, the urban ventilation environment under different wind directions and seasons was analyzed. This method can effectively express the ventilation conditions throughout the whole study area and can simultaneously express the quality of the generated corridors effectively. The results show that Wuhan has three levels of ventilation corridor. Moreover, the ventilation conditions in Wuchang (Wuchang, Qingshan, and Hongshan) are better than those in Hankou (Qiaokou, Jianghan, and Jiang’an).